Female Friendships in the Ancient Greek Novels - Mercer, Laura Christine (2023)
This project examines the female friendships within the Ancient Greek Novels, focusing on four of the five surviving "idealistic" novels (Aethiopica (Heliodorus), Callirhoe (Chariton), Ephesian Tale (Xenophon of Athens) and Leucippe and Clitophon (Achilles Tatius)) as well as Iamblichus' fragmentary Babyloniaca.